Teaching Ph.D. students to teach political science: the Emory TATTO program. - Knotts, H. Gibbs; Main, Eleanor C. (PS: Political Science & Politics, 1999)
The writers discusses the Teacher Assistant Training and Teaching Opportunity Program (TATTO) in operation at Emory University. They explain that participation in TATTO is intended to prepare graduate students to enter the professoriate as competent and confident teachers, with the ultimate aim being to guarantee that each student's education as a research scholar is balanced with thoughtful and thorough preparation in the art of teaching. They consider the five components of Emory's TATTO program and outline how the program has evolved within the political science department. They identify the strengths of TATTO and pinpoint the problems that have arisen and the steps that have been taken to resolve them. Finally, they suggest which parts of the program could be most easily replicated at other universities.